RANCANG BANGUN TURBIN AIR TIPE CROSSFLOW DAN PENGARUH KETINGGIAN AIR TERHADAP EFISIENSI TURBIN UNTUK PEMBANGKIT LISTRIK TENAGA PIKOHIDRO - Yogi Permana; Ahmad Jaya; Muhammad Hidayatullah; Nova Aryanto (Program Studi Teknik Elektro, 2023)
Pico Hydro Power Plant (PLTPH) is one of the innovations for the use of alternative energy so that it can increase the role and potential of existing water energy sources in an area. The research method used is the experimental method by doing type water turbine design cross flow as a prime mover for a Laboratory-scale Pico-Hydro Power Plant. There are 2 parameters for the success of this study, namely being able to make a cross flow type water turbine with a turbine rotational speed of 100 Rpm and varying the water level to determine the performance of a cross flow type water turbine. The results of the water turbine design crossflow with a diameter of 15 cm, the number of turbine blades type cross flow 13 blades, the rotational speed of the turbine without load is 299.5 Rpm while the turbine rotation with an AC generator load is 195.5 Rpm, the power generated is 0.509 Watt with a turbine efficiency of 1.5%.